2013
DOI: 10.1002/jms.3278
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of N‐Boc/Fmoc/Z‐N′‐formyl‐gem‐diaminoalkyl derivatives using electrospray ionization multi‐stage mass spectrometry

Abstract: N-Boc/Fmoc/Z-N'-formyl-gem-diaminoalkyl derivatives, intermediates particularly useful in the synthesis of partially modified retro-inverso peptides, have been characterized by both positive and negative ion electrospray ionization (ESI) ion-trap multi-stage mass spectrometry (MS(n)). The MS(2) collision induced dissociation (CID) spectra of the sodium adduct of the formamides derived from the corresponding N-Fmoc/Z-amino acids, dipeptide and tripeptide acids show the [M + Na-NH2CHO](+) ion, arising from the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Tandem mass spectrometry analysis of a building blocks 2 and 3 containing the nitrogen orthogonalizing group tertbutyloxycarbonyl (Boc, Fig. 2c) 29 , and the oxygen orthogonalizing group tetrahydropyran (THP, Fig. 2d) 30 showed that each readily lost diagnostic chemical fragments (56 and 84 Da respectively) and were thus NL-ADE-MS compatible.…”
Section: Simplified Parameterizationmentioning
confidence: 99%
“…Tandem mass spectrometry analysis of a building blocks 2 and 3 containing the nitrogen orthogonalizing group tertbutyloxycarbonyl (Boc, Fig. 2c) 29 , and the oxygen orthogonalizing group tetrahydropyran (THP, Fig. 2d) 30 showed that each readily lost diagnostic chemical fragments (56 and 84 Da respectively) and were thus NL-ADE-MS compatible.…”
Section: Simplified Parameterizationmentioning
confidence: 99%